Pengaruh Literasi Keuangan Digital Dan Kondisi Sosial Ekonomi Orang Tua Terhadap Pengeluaran Konsumsi Mahasiswa (Studi Kasus Mahasiswa Generasi Z Di Kota Jambi) - Muhammad Irgiansyah; Zamzami .; Jaya Kusuma Edy (Journal of Islamic Banking, 2025)
The development of e-wallets, mobile banking, fintech, and paylater features facilitate transactions and expand consumption choices for Generation Z students. This study aims to (1) describe the socioeconomic characteristics of parents of Generation Z students in Jambi City, (2) analyze the influence of digital financial literacy on student consumption expenditure, and (3) examine the influence of parents' socioeconomic conditions on student consumption expenditure. The study used a quantitative approach with a survey method and primary data through questionnaires on 156 respondents. The variables of digital financial literacy (X1) and parents' socioeconomic conditions (X2) were measured using the Guttman scale (1/0), while student consumption expenditure (Y) was measured on a ratio scale. The analysis was carried out through validity tests, reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and coefficients of determination. The results showed that digital financial literacy had a positive and significant effect on student consumption expenditure, while parents' socioeconomic conditions did not have a significant effect partially. However, both variables simultaneously had a significant effect on consumption expenditure with a very high model explanatory power. This finding confirms that in the context of Generation Z students, the intensity and ease of digital transactions are more dominant factors in explaining variations in spending than family background